Pengaruh Penggunaan Metode Observasi terhadap Kemampuan Klasifikasi Siswa Kelas X SMAN 7 Bekasi - Zulfah Zulfah; Budhi Akbar; Sahami Abdullah (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2021)
This research aims to know the effect of the observation method used toward the classification ability of student in grade X. This research was conducted in the first semester of academic year 2015/2016 in october-november, SMAN 7 Bekasi. The method used quasi experiment method. Population in this research were all students of X MIA class at SMAN 7 Bekasi 2015/2016, the sample were X MIA 4 class with 30 pupils and X MIA 5 with 32 pupils. The research sample was taken by cluster random sampling technique. The instrument used in this research were test instrument. Instrument test contains 20 questions of the classification ability, the instrument has been tested with the validity teste in XI IPA 1. The research exhibit that the type of classification ability was more controlled by the experimental class. It can be seen in the persentage owned by the experimental class in each indicator of the ability of classification, with the largest percentage in catagorizing indicators at 87,22%. The average value of the experimental group was 77,30 with a standard deviation at 9,16 and an average value in the control group was 57,03 with a standard deviation at 8,96. In the t test of the calculation results obtained value thit = 8,95 and t0,99 = 2,66. Because it was greater than t table then H0 rejected and H1 accepted. Thus, it can be concluded that there are significant observations of the ability to use the classification method in class X on the matter of biodiversity in SMAN 7 Bekasi.